156 Major Depression is Linked to Increased Information Flow From the Orbitofrontal Cortex. (April 2023) - Myers, John; Xiao, Jiayang; Metzger, Brian; Adkinson, Joshua; Allawala, Anusha; Pirtle, Victoria; Mathura, Raissa; Anand, Adrish; Gadot, Ron; Najera, Ricardo Andres; Rey, Hernan Gonzalo; Shofty, Ben; et al.
Abstract : INTRODUCTION: Major depression is associated with widespread dysfunction throughout the limbic system and neocortical regions such as the orbitofrontal cortex (OFC) and the dorsolateral prefrontal cortex (dlPFC) (4–7). The brain regions comprising the limbic system, including the amygdala, ventral striatum, and anterior cingulate cortex (ACC), show altered connectivity in MDD patients (5, 7). As part of an ongoing NIH-funded trial of DBS for depression, we implanted 3 patients with both DBS leads and stereo-EEG (sEEG) electrodes to measure neural oscillations in the dlPFC, OFC, and ACC. METHODS: Three depression patients were implanted with sEEG electrodes in areas including OFC, dlPFC, and ACC. We frequently measured depression severity throughout a 9-day inpatient monitoring period using a validated adaptive severity scale (8). We measured directed connectivity using multivariate vector autoregressive models that measure information flow between the right dlPFC, OFC, and ACC during resting state). Then we examined the relationship between depression severity and GC within the delta band (1-3 Hz). RESULTS: Information flow within the delta band was positively correlated with depression severity in each patient. Each showed distinct patterns of pathophysiological connectivity. Across all patients, directed connectivity from the OFC to the ACC predicted depression severity (p < 0.05). CONCLUSIONS: Information flow within the prefrontal cortex correlates closely with depression severity. Increased OFC -> ACC connectivity may relate to increased self-appraisals of mood and diminished control of emotional state during depressive episodes.